ANALISIS KESEMPATAN KERJA PADA SEKTOR PARIWISATA (SUB SEKTOR PERHOTELAN) DI PROVINSI-PROVINSI INDONESIA - Fitri Yulianti; Sri Ulfa Sentosa (Jurnal Ecogen, 2018)
This research purpose are to the analyse how the impact of the number of accommodation business, number of visitors to accommodation, output of the hotel sector and the wage on the employment opportunities of the hotel sector in the Indonesian Provinces using the panel regression method based on the fixed effect model (FEM) approach. This type of research is descriptive and associative research, where the data used are secondary data in the form of panel data (pool time series) from 33 provinces in Indonesia during the period 2012-2016. The results of this study indicate that the variable number of business accommodations, the number of visitors to accommodation has a positive and significant effect on the employment opportunities in the hotel sector in the Indonesian Provinces, the hotel sector's output variables have a positive but insignificant effect on the hospitality sector employment opportunities in the Indonesian Provinces and wages have a non-significant negative influence on the employment opportunities in the hotel sector in the Indonesian Provinces.Keywords: Hospitality Sector Job Opportunities, Accommodation Business, visitors to accommodation, Hospitality Sector Output, Wage